Fiber Bragg gratings in heterogeneous multicore fiber for directional bending sensing. (20th July 2016) - Zhang, Hailiang; Wu, Zhifang; Shum, Perry Ping; Wang, Ruoxu; Dinh, Xuan Quyen; Fu, Songnian; Tong, Weijun; Tang, Ming
Abstract: We present the fabrication of fiber Bragg gratings (FBGs) in a trench-assisted heterogeneous multicore fiber (MCF). Two obviously different Bragg reflection peaks are obtained due to the slight difference of refractive indices between the center core and the outer cores. To investigate the reflections of the two FBGs simultaneously, only a segment of multimode fiber is inserted between the lead-in single mode fiber and the MCF. The experimental results confirm that the curvature sensitivity of the FBG in the outer core is a sinusoidal function of the bending orientation angle. The maximum linear curvature sensitivity is about 0.128 nm/m −1 . The cross sensitivity to temperature or externally applied axial strain can be eliminated by discriminating the different responses of FBGs inscribed in outer cores and the center core. Thus this MCF with FBGs can be utilized as a directional bending sensor. Moreover, the proposed sensor offers several advantages, such as low cost and flexibility in fabrication.